Absence of antiretroviral therapy and other risk factors for morbidity and mortality in Malaysian compulsory drug detention and rehabilitation centers - Fu, J.J.; Bazazi, A.R.; Altice, F.L.; Mohamed, M.N.; Kamarulzaman, A. (Public Library of Science, 2012)
Background: Throughout Asia, people who use drugs are confined in facilities referred to as compulsory drug detention and rehabilitation centers. The limited transparency and accessibility of these centers has posed a significant challenge to evaluating detainees and detention conditions directly. Despite HIV being highly prevalent in this type of confined setting,direct evaluation of detainees with HIV and their access to medical care has yet to be reported in the literature. Methods: We evaluated the health status of 100 adult male detainees with HIV and their access to medical care in the two largest Malaysian compulsory drug detention and rehabilitation centers holding HIV-infected individuals. Results: Approximately 80% of all detainees with HIV were surveyed in each detention center. Most participants reported multiple untreated medical conditions. None reported being able to access antiretroviral therapy during detention and only 9% reported receiving any HIV-related clinical assessment or care. Nearly a quarter screened positive for symptoms indicative of active tuberculosis, yet none reported having been evaluated for tuberculosis. Although 95% of participants met criteria for opioid dependence prior to detention, none reported being able to access opioid substitution therapy during detention, with 86% reporting current cravings for opioids and 87% anticipating relapsing to drug use after release. Fourteen percent of participants reported suicidal ideation over the previous two weeks. Conclusion: We identified a lack of access to antiretroviral therapy in two of the six compulsory drug detention and rehabilitation centers in Malaysia designated to hold HIV-infected individuals and found significant, unmet health needs among detainees with HIV. Individuals confined under such conditions are placed at considerably high risk for morbidity and mortality. Our findings underscore the urgent need for evidence-based drug policies that respect the rights of people who use drugs and seek to improve, rather than undermine, their health.